Beyond Verbal Behavior: An Empirical Analysis of Speech Rates in Psychotherapy Sessions - Rocco, Diego; Pastore, Massimiliano; Gennaro, Alessandro; Salvatore, Sergio; Cozzolino, Mauro; Scorza, Maristella (Frontiers in Psychology, 2018)
Objective: The present work aims to detect the role of the rate of speech as a mechanism able to give information on patient’s intrapsychic activity and the intersubjective quality of the patient–therapist relationship. Method: Thirty clinical sessions among 5 patients were sampled and divided into idea units (N = 1276) according to the referential activity method. Each idea unit was rated according to referential activity method and in terms of speech rate (syllables per second) for both patient and therapist. A mixed-effects model was applied in order to detect the relationship between the speech rate of both the patient and the therapist and the features of the patient’s verbal production in terms of referential activity scales. A Pearson correlation was applied to evaluate the synchrony between the speech rate of the patient and the therapist. Results: Results highlight that speech rate varies according patient’s ability to get in touch with specific aspects detected through referential activity method: patient and the therapist speech rate get synchronized during the course of the sessions; and the therapist’s speech rate partially attunes to the patient’s ability to get in touch with inner aspects detected through RA method. Conclusion: The work identified speech rate as a feature that may help in the development of the clinical process in light of its ability to convey information about a patient’s internal states and a therapist’s attunement ability. These results support the intersubjective perspective on the clinical process.